On the Seidel Laplacian spectrum of threshold graphs - Megha P M; Parvathy K S (Journal of Hyperstructures, 2024)
A graph which does not contain C4, P4, or 2K2 as its induced subgraphs, is called a threshold graph. In this paper, we consider seidel laplacian matrix of a connected threshold graph and determine the seidel laplacian spectrum. Also, the characterization of threshold graphs having atmost four distinct seidel laplacian eigenvalues have been computed.